DESAIN DAN UJI COBA HANDOUT DENGAN PENDEKATAN CONTEXTUAL TEACHING AND LEARNING (CTL) BERBASIS GUIDED NOTE TAKING PADA MATERI LAJU REAKSI - Dinni Novrida; Fitri Refelita (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2022)
This research was instigated by the importance of interesting teaching material availability on Chemistry subject. This research aimed at designing an interesting chemistry teaching material for students in order to increase educational quality, then validity test was conducted by the experts of media and material, practicality test was by Chemistry subject teacher, and trial was to the students. In this research, the handout was designed by using Guided Note Taking based Contextual Teaching and Learning (CTL) approach on Reaction Rate lesson. The final product was in the form of a valid handout. It was Research and Development (R&D) with Borg and Gall modification model, and it was administered at State Senior High School Plus Riau Province. Interview, questionnaire, and documentation were the techniques of collecting the data. The handout with Guided Note Taking based CTL approach on Reaction Rate lesson developed was tested valid with the percentage 91.72% (very valid), it was tested practical with the percentage 88.33% (very practical), and it got good response to all handout contents with the percentage 93.54% (very good). Based on these findings, it could be concluded that the handout with Guided Note Taking based CTL approach on Reaction Rate lesson was valid and practical, and it got good student response, so it could be done the test on the next step.Keywords : Handout, Contextual Teaching and Learning (CTL), Guided Note Taking, Reaction Rate